RESPONSIBILITY AND LEGAL AWARENESS OF SEA TRANSPORT SERVICE PROVIDERS TO PREVENT POLLUTION OF THE MARINE ENVIRONMENT IN THE MALAKA STRAIT AREA - Fadlan Fadlan (Badan Penerbit STIEPARI Press, 2023)
Based on the problems above, the prevention principle was first introduced at the United Conference on Environment and Development (UNCED) in Rio de Janeiro in 1992, better known as the Rio Declaration 1992. This principle states that to protect the environment, every country should be able to apply an approach to prevention by their respective abilities. UNCLOS 1982, as a law of the sea convention that has been widely accepted by countries around the world, also regulates explicitly the protection of the marine environment. In Chapter XII on protecting and preserving the Marine Environment, article 192 states that States are obliged to protect and preserve the marine environment. This also applies to the Strait area, one of a country's sea areas. Pollution of the marine environment is a change in the marine environment that occurs as a result of the direct or indirect introduction by humans of materials or energy into the marine environment (including river mouths), which results in such harmful consequences that it constitutes a loss to biological wealth, a hazard to human health. , disturbance to activities at sea, including fishing and others, reasonable use of the sea, deterioration of seawater quality, and reduction of places of residence and recreation. One of the problems in this research is how the principles contained in the laws and regulations are a basis for preventing pollution of the marine environment in the Malacca Strait. The research method used in this study is a normative juridical method considering that the starting point of this research is an analysis of laws and regulations governing marine environmental pollution.